How progressives took advantage of moderate discontent: political opportunity, framing and mobilization at the local level - Fisher, Sara L. (Kansas State University, 2007)
This paper asks why a progressive social movement formed in a conservative place. The People for a Progressive University City (PPUC) formed as a Political Action Committee (PAC) in a mid-sized community in order to influence the city commission and school board election of 2005. Resource Mobilization theory assumes that social movements form when they have access to resources including money, networks and leadership (Barkan 1979, McCarthy and Zald 1977). Political Opportunity theory assumes that social movements form when opportunities for mobilization are visible (Goodwin, Jaspers and Jaswin 1999, Tarrow 1996). The Framing Perspective assumes that social movements form when they describe grievances and their solutions in a way that is reasonable to potential participants (Benford and Snow 2000, Gamson and Modigliani 1989). I have taken an Action Research approach to understand what developments led to the organization’s formation and which theory best described why the movement formed in 2005. Through 31 in-depth interviews with community members, I concluded that no one theory alone can explain why the organization formed. I argue that the best theoretical explanation is a synthesis of all three. I outline several theoretical implications as well as practical implications for community organizing in University City. I argue that the future of the PPUC will depend on how it responds to changes in community discontent and if it is able to mobilize people. Additionally, I suggest the story of the PPUC has implications for the study of social movements in general.
Keywords: Social Movement; Local; Political Action Committee; Resource Mobilization; Political Opportunity; Framing; Sociology, General (0626)